ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AND ITS IMPORTANT ROLE ON PARAMEDIC PERFORMANCE OF PUSKESMAS IN EAST OKU DISTRICT - Margahana, Helisia; Saputra, Wahid Eka; Harlofida, Demsi; sahrita, Yan (DIA: Jurnal Administrasi Publik, 2019)
An organization needs to have qualified employees who are willing to work outside their main duties to support performance. This willingness is called organizational citizenship behavior (OCB). The problem faced by health centers as public health service providers is how the Organizational Citizenship Behavior (OCB) improves the Performance of Community Health Center Paramedics in East OKU District, while the purpose of this study is to determine the Organizational Citizenship Behavior (OCB) and its important role in the Performance of Health Center Paramedics in East OKU Regency. . The hypothesis proposed is that Organizational Citizenship Behavior (OCB) plays an important role in improving the performance of public health center paramedics in East OKU district. From the calculation results obtained r = 0.318 after being consulted with a conservative standard to determine whether or not this effect is strong, it turns out that r = 0.318. after consultation with the conservative standard, it turns out that 0.318 lies between 0.200 - 0.399 which is included in the low correlation. Then to answer the hypothesis test that was previously proposed to have a relationship or not, then tested with the hypothesis test and obtained t = 0.671. so when connected to the t table value with a confidence level of 95%, which means the error rate of 5% (0.05) is t count smaller than t table, namely 0.671 <(0.05: 4) = 2.132. Thus, it means that Ha is rejected, Ho is accepted, this means that there is a low influence between the Organizational Citizenship Behavior (OCB) on improving the performance of the Puskesmas Paramedics in East OKU Regency.